Human resource management : managing employees for competitive advantage - Lepak, David; Gowan, Mary (Upper Saddle River, NJ : Pearson/Prentice Hall, 2010)
This text seeks to help students understand the dynamic and exciting environment of human resources (HR) management and the complex decisions that all managers must make when managing employees.
Includes bibliographical references (p. 435-461) and indexes.
Keywords: Personnel management; Supervision of employees